Pengembangan Media Bimbingan Konseling Permainan Monopoli Truth And Dare Untuk Meningkatkan Self Confidence Pada Peserta Didik - Azmi Septiani Thalib (Universitas Negeri Makassar, 2021)
This study developed truth and dare monopoly counseling guidance media to increase self-confidence in students. The focus of this research is: 1) How is the description of the service needs of the truth and dare game counseling guidance media effective in increasing self-confidence in students at SMP Negeri 8 Makassar ?, 2) What is the level of validity of the truth and dare game monopoly game counseling guidance media to be applied to students at SMP Negeri 8 Makassar ?, 3) What is the level of acceptance of the truth and dare monopoly game counseling guidance media to be applied to students at SMP Negeri 8 Makassar? The purpose of this study was to find out: 1) Knowing the description of the service needs of the truth and dare monopoly game counseling guidance media is effective in increasing self-confidence in students at SMP Negeri 8 Makassar, 2) Knowing the level of validity of the truth and dare game counseling guidance media for applied to students at SMP Negeri 8 Makassar, 3) Knowing the level of acceptance of the truth and dare monopoly game counseling guidance media to be applied to students at SMP Negeri 8 Makassar. This study uses the Research and Development (RnD) research method, by collaborating qualitative and quantitative research. The data collection technique used was the Material and Media Expert Validation Sheet to determine the validity of the media and the Student Response Questionnaire. The analysis technique used is the form and descriptive analysis technique. So the results showed that the truth and dare monopoly developed was valid and practically used for providing guidance and counseling services at SMP Negeri 8 Makassar